2016
DOI: 10.1021/acsinfecdis.6b00124
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Supplementation Improves Phenylalanine Metabolism in a Murine Model of Severe Malaria

Abstract: Tetrahydrobiopterin (BH4) is an essential cofactor for both phenylalanine hydroxylase and nitric oxide synthase. Patients with severe malaria have low urinary BH4, elevated plasma phenylalanine, and impaired endothelium-dependent vasodilation, suggesting that BH4 depletion may limit phenylalanine metabolism and nitric oxide synthesis. We infected C57BL/6 mice with Plasmodium berghei ANKA to characterize BH4 availability and to investigate the effects of BH4 supplementation. P. berghei ANKA infection lowered BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been shown that eNOS S -glutathionylation can trigger BH 4 depletion resulting in further eNOS uncoupling with loss of NO production and enhanced superoxide generation. BH 4 depletion has been shown to occur in a variety of animal and human disease models ( 45 , 46 ), although human studies of oral BH 4 replacement therapy have yielded mixed results ( 47 ). Interestingly, BH 4 supplementation (10 mg/kg/day) significantly decreased various types of congenital heart defects in the embryos of pregestational diabetic mice ( 42 ), suggesting the importance of sufficient antioxidant and anti-inflammatory compounds during pregnancy.…”
Section: Oxidative Stress Enos Uncoupling and Vedmentioning
confidence: 99%
“…Furthermore, it has been shown that eNOS S -glutathionylation can trigger BH 4 depletion resulting in further eNOS uncoupling with loss of NO production and enhanced superoxide generation. BH 4 depletion has been shown to occur in a variety of animal and human disease models ( 45 , 46 ), although human studies of oral BH 4 replacement therapy have yielded mixed results ( 47 ). Interestingly, BH 4 supplementation (10 mg/kg/day) significantly decreased various types of congenital heart defects in the embryos of pregestational diabetic mice ( 42 ), suggesting the importance of sufficient antioxidant and anti-inflammatory compounds during pregnancy.…”
Section: Oxidative Stress Enos Uncoupling and Vedmentioning
confidence: 99%
“…Under normal circumstances, about 50% of the PA consumed is used to synthesize proteins of various components, and the rest is converted to tyrosine under the action of PA hydroxylase and then converted into dopamine, epinephrine, norepinephrine, and melanin. When PA hydroxylase is lacking, these metabolites reach abnormally high levels and accumulate in tissues, plasma, and cerebrospinal fluid, which are excreted in large quantities from the urine ( Alkaitis and Ackerman, 2016 ). PA level in blood sample was decreased after TFN treatment involved in PA, tyrosine, and tryptophan biosynthesis and PA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, about 50% of the PA consumed is used to synthesize proteins of various components, and the rest is converted to tyrosine under the action of phenylalanine hydroxylase, and then converted into dopamine, epinephrine, norepinephrine, and melanin. When PA hydroxylase is lacking, these metabolites reach abnormally high levels and accumulate in tissues, plasma, and cerebrospinal fluid, which are excreted in large quantities from the urine (Alkaitis and Ackerman, 2016). Taurocholic acid can reduce capillary permeability of inflammatory tissues, inhibit inflammatory swelling, and restrain the production of inflammatory mediators such as NO, PGE2, and histamine.…”
Section: Discussionmentioning
confidence: 99%